THE COMPARISON BETWEEN CONVENTIONAL, SHARIA, AND SOCIAL INSURANCE IN INDONESIA - Bagas Heradhyaksa; Nurul Hikmah (Fakultas Hukum, Universitas Diponegoro, 2019)
Insurance is a risk transfer agreement from the insured to the guarantor. Insurance is a financial institution whose development is quite rapid, both in the world and in Indonesia. Insurance in Indonesia has three forms, namely conventional, sharia, and social. Social Security Organizing Board in Indonesia named BPJS (Badan Penyelenggara Jaminan Sosial). Although all of them are the forms of insurance but has several differences. The fundamental differences are juridical differences and philosophical differences. The purpose of this study is to determine the juridical differences and philosophies of conventional, sharia, and social insurance. This research uses the juridical normative method. This method is used to analyze differences in conventional, sharia and social insurance by studying legal data related to the field. The results of this study found that the legal basis used in conventional, sharia, social insurance has differences. The philosophy of conventional insurance, sharia, and social also has differences. Therefore, although they are both in the form of insurance, conventional, sharia, and social insurance have significant differences respectively.